Avifaunal use of an artificial waterpoint in the Strzelecki Desert during an extended dry period. (2nd October 2021) - Gorta, Simon B. Z.; Pedler, Reece D.; Kingsford, Richard T.; Callaghan, Corey T.
ABSTRACT: Dryland ecosystems have limited and patchily distributed water – a vital resource for species in these landscapes. Degradation of these ecosystems is increasing due to climate change and understanding species' responses to this drying is critical for effective ecosystem management. During an extended dry period, we surveyed drinking visits of an avian community at an artificial waterpoint in semi-arid Australia. Opportunistically, a small rainfall event punctuated the survey, enabling comparisons of avian visitations, before and after the event, as a proxy for increased water availability in the landscape. Visitations of drinking birds to the waterpoint before the rainfall event (17 species) were significantly higher than after (3 species). Permanent waterpoints, such as the single site surveyed in this study, can sustain avifauna during extended dry periods in drylands, affecting spatio-temporal and potentially functional avian community dynamics. Periodic reliance of dryland birds on permanent water may increase with prolonged droughts under climate change, and this reliance must be considered alongside the negative ecological consequences of permanent waterpoints in the management of these ecosystems.